Development Of Fed-Batch Cultivation Process For Esherichia Coli Harboring Superoxide Dismutase - Wan Omar, Wan Siti Atikah (2009)

(untitled)
The fed-batch cultivation process for the production of the recombinant protein, superoxide dismutase (SOD) by E. coli BL21 (DE3) pLysS was carried out. The cultivation process for recombinant SOD (ESOD) production was optimized through several approaches and strategies. The first approach was to optimize medium and culture conditions of the ESOD culture in shake flask via conventional and the Response Surface Methodology (RSM) methods. Laboratory scale batch cultivation of ESOD was then performed using a 2 L stirred tank bioreactor (STB) in order to further optimize the medium and culture conditions. The effects of glucose concentrations (15 and 20 g/L), agitation speeds (300 – 1000 rpm) and controlled dissolved oxygen tension (DOT) via agitation speeds (20%, 50% and 80%) on the growth performance of the recombinant E. coli strain were investigated. In the final stage, fed-batch techniques were applied to the process for the development of high cell density cultivation. The performance and kinetics of the ESOD fed-batch and batch cultivations were then evaluated and compared.